Epicuticular wax content of western white pine is involved in Cronartium ribicola resistance. Issue 1 (20th January 2023) - Noshad, David; Ukrainetz, Nicholas; King, John; Yanchuk, Alvin
Abstract: The introduction of Cronartium ribicola, the causative agent of white pine blister rust, has been devastating for white pines in North America, including western white pine. Among the observed partial resistance responses to white pine blister rust is a mechanism referred to as difficult‐to‐infect (DI), which is characterized by lower frequency of infection spots on needles and a lower incidence of branch and stem cankers than susceptible host plants. Parents with the DI trait were selected and bred to produce nine full‐sib families. Progeny were propagated and cloned using in vitro techniques in controlled environmental conditions. Explants were inoculated with a single strain of C. ribicola and characterized by using a disease assessment index (DAI), which was used to compare DI full‐sib families to several other full‐sib families (from Idaho) selected for other partial resistance traits. Most DI families had significantly lower DAI scores and higher epicuticular wax content. When the wax was removed from the surface of needles, the DAI of all full‐sib families increased. Scanning electron microscopy revealed that stomata in DI full‐sib families are mostly occluded by epicuticular wax. The results of this study suggest that the DI resistance mechanism of western white pine is related to needle surface epicuticular wax, which likely hinders the penetration of stomata by fungal hyphae. The occurrence and magnitude of this trait in the breeding population remains unknown, and special assessment technique for large‐scale screening will have to be developed.